A 25-Year Review of Customer Relationship Management Research in Indonesia: Evolution, Trends, and Future Directions - Yeane Koyongian; Deske W. Mandagi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Academic interest in Customer Relationship Management (CRM) has grown substantially, reflecting its strategic importance in enhancing customer value, loyalty, and organizational performance. This study systematically reviews and maps the evolution and dominant themes of CRM research in Indonesia over 25 years (2000–2025). Using a systematic literature review (SLR) of the Scopus database, 469 articles were initially identified and filtered to 226 final studies based on inclusive criteria. Bibliometric mapping and content analysis reveal six major research clusters: customer satisfaction and value; supply chain management and sustainability; business and marketing performance; loyalty and consumer behavior; relationship and customer management; and management and organizational issues. The review also identifies emerging themes, including artificial intelligence and big data analytics in CRM, omnichannel customer management, sustainable customer relationships, and the influence of Indonesia’s cultural and institutional context. By synthesizing established and emerging research streams, this study provides a comprehensive overview of CRM scholarship in Indonesia and offers directions for future theoretical and empirical research.